Perceptions of critical and emergency department nurses regarding changes in their professional role - Maria NK Karanikola; Margarita Giannakopoulou; Meropi Mpouzika; Christiana Nicolaou; George Tsiaousis; Foteini Vouzavali; Anna Koutroubas; Elizabeth DE. Papathanassoglou (SciELO, 2018)
ABSTRACT Objective Preliminary investigation of the way Greek critical and emergency department nurses conceptualize changes in their professional role. Method A qualitative focus-group methodology was applied. Following purposeful sampling and informed consent of participants. Results Participated eight individuals. The need for enhancement of nurses' participation in decision-making in order for an actual change in their professional role to be achieved was the central theme of participants' narratives. Perceived advancements in professional role performance regarded: evidence-based practice; technology; education, knowledge; clinical skills; research; heightened nurse-physician collaboration. Perceived reasons why these advancements failed to enhance nurses' professional role were lack of meritocracy; competitive relationships; lack of support among nurses; insufficient managerial support; budget limitations. Conclusion Despite advancements in clinical practice, participants did not deem that their professional role was enhanced significantly, as participation in decision-making and control over practice remain limited. Interventions targeted to enhance nurses' participation in clinical decision-making, and overall professional autonomy are recommended.